2015
DOI: 10.1200/jop.2015.005173
|View full text |Cite|
|
Sign up to set email alerts
|

Systematic Approach to Providing Breast Cancer Survivors With Survivorship Care Plans: A Feasibility Study

Abstract: It is feasible to identify and deliver SCPs to women with breast cancer who are approached during the postoperative visit in a surgical clinic. Additionally, SCPs seem to improve patient knowledge in several areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Caregiver experience was often examined as an outcome indicator for integrated care plans focused on the palliative stage of care [ 87 92 ]. Provider-level outcomes included provider satisfaction with the use of integrated care plans, i.e., workflow interruptions, ease of use, time associated with generating or discussing the integrated care plan with patients [ 74 83 ], and provider’s perceptions of benefits (i.e., improvements in information sharing between providers) [ 71 74 79 80 83 98 ]. System-level indicators included common healthcare utilization measures such as length of stay, complication rates (post-operative), hospital readmissions, and cost (hospital-related costs and the cost of delivering the integrated care plan) [ 36 39 40 41 43 46 47 48 49 51 54 55 56 57 58 60 61 67 85 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Caregiver experience was often examined as an outcome indicator for integrated care plans focused on the palliative stage of care [ 87 92 ]. Provider-level outcomes included provider satisfaction with the use of integrated care plans, i.e., workflow interruptions, ease of use, time associated with generating or discussing the integrated care plan with patients [ 74 83 ], and provider’s perceptions of benefits (i.e., improvements in information sharing between providers) [ 71 74 79 80 83 98 ]. System-level indicators included common healthcare utilization measures such as length of stay, complication rates (post-operative), hospital readmissions, and cost (hospital-related costs and the cost of delivering the integrated care plan) [ 36 39 40 41 43 46 47 48 49 51 54 55 56 57 58 60 61 67 85 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although improving knowledge alone is not sufficient to improve care coordination, it is a necessary component. To date, no randomized controlled study has examined whether SCPs have an impact on survivor knowledge, although 2 studies 15,19 have demonstrated improvements in assessed Cancer March 15, 2019 knowledge using surveys before and after SCP receipt. Although we also demonstrated an improvement in survivor knowledge, this change was likely unrelated to SCP provision.…”
Section: Discussionmentioning
confidence: 99%
“…15,18,19 Without a control group, it is difficult to separate change driven by increasing familiarity, because surveys are repeated or participants seek out knowledge in response to a survey question rather than learning from the SCP or care-planning visit. 15,18,19 Without a control group, it is difficult to separate change driven by increasing familiarity, because surveys are repeated or participants seek out knowledge in response to a survey question rather than learning from the SCP or care-planning visit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reflecting this, centres in North America have the most experience with survivorship care planning though they are now in use in many countries [8]. SCPs improve engagement with patients' general practitioners [9,10], facilitate discussion between patients and their families [10,11] and are associated with higher levels of satisfaction [12], knowledge [13] and self-reported understanding by survivors [11,12].…”
Section: Livestrong Tm Scp Developed In 2007) Function As a Communicmentioning
confidence: 99%